Avaliação da ventilometria e espirometria no pré e pós-operatório de pacientes submetidos à cirurgia de hipertensão portal - Araújo Filho, Amaro Afrânio (2007)
The main goal of the present study is to assess and compare the data obtained from ventilometry, espirometry and vital signs of patients who undergoing DAPE under inhalation anesthesia, and its specific goal is to verify the existence of a co-relation between anesthetic and surgical procedure lengths and pulmonary volumes measured by ventilometry and espirometry during the DAPE post-operative period. The subjects were adult patients between 43,3 ± 13,4 years of age, being 8 males and 5 females admitted at the surgery clinic of the Federal University Hospital in Aracaju, Sergipe, Brazil, with a previous diagnosis of portal hypertension. It is a prospective study, with the data collection being carried out in two phases: pre-operative and post-operative stages. Researched variables: age; gender; heart rate (HR); respiratory frequency (RF); blood pressure (BP); partial oxygen saturation (PSO2); minute volume (MV); current volume (CV); forced expiratory volume in 1 second (FEV1); forced vital capacity (FVC); tifeneau index (FEV1/ FVC); surgery length; anesthesia length. The statistical analysis was performed by the Origin 6.2. software. To compare the averages of BP, HR, PSO2, MV, CV, FEV1, FVC and FEV1/ FVC in both pre and post-operative stages the T test Dependent or Paired Student test. To analyses the variance the Fisher test was applied. For the co-relation between anesthetic and surgical procedure length and MV, CV, FEV1 and FVC in the post-operative stage the Pearson simple linear co-relation test was applied. For statistical tests, a 95% (α=0,05) significance level was utilized. Results showed that there was a significant difference between the mean values of HR, RF, BP, MV, CV, FEV1, FVC and PSO2. There was no significant difference between the mean values of FEV1/ FVC. Reversely, the co-relation between surgery length and the pulmonary values measured on day 2 of the post-operative period was significant of strong aspect when compared to FEV1 and FVC, and suggested a non-significant co-relation in regular aspect when compared to MV and CV. Anesthesia length showed a significant co-relation in a strong aspect when compared to FEV1 and FVC, and suggested a non-significant co-relation of weak aspect when compared to MV and of regular aspect when compared to CV. It has been concluded that patients who have undergone portal hypertension surgery present significant reduction in MV, CV, FEV1, FVC and PSO2, in addition to a significant rise in HR, BP and RF when compared to the preoperational and day 2 of post-operative period. Moreover, a significant co-relation of strong aspect was detected when anesthetic and surgical procedure lengths were compared to post-operative FEV1 and FVC values.